Extracorporeal cardiopulmonary resuscitation at the emergency department: A retrospective patient selection evaluation. Issue 4 (April 2020) - Poppe, Michael; Schriefl, Christoph; Steinacher, Anna; Clodi, Christian; Warenits, Alexandra-Maria; Nürnberger, Alexander; Hubner, Pia; Holzer, Michael; Horvat, Johann; Wiedemann, Dominik; Weiser, Christoph
Abstract : BACKGROUND: There is an increasing use of extracorporeal life support in refractory cardiac arrest. Recent studies highlighted the importance of an early and accurate patient selection for this invasive procedure. OBJECTIVES: The aim of this study was to retrospectively validate a six-criteria-screening-checklist (witnessed collapse, bystander-cardiopulmonary resuscitation/first medical contact <5 min, shockable, age <70 years, end tidal carbon dioxide >14 mmHg and pupils not anisocoric/distorted/mydriatic) as an early screening tool in patients treated with extracorporeal cardiopulmonary resuscitation (eCPR) at the emergency department. DESIGN: Retrospective observational study. SETTING/PATIENTS: All patients at least 18 years of age with nontraumatic cardiac arrest and without return of spontaneous circulation before eCPR treatment at our department between January 2013 and December 2018 were included in this retrospective observational study. INTERVENTION: No specific intervention was set in this observational study. MAIN OUTCOME MEASURES: Primary outcome was the rate of patients who fulfilled all criteria, secondary outcome was 30-day and 6-month survival in accordance with the criteria. RESULTS: Overall, data from a total of 92 patients were eligible for analyses. Out of these, 27 patients (29%) met all criteria. Patients, who fulfilled all criteria, showed significantly higher odds for 30-day survival [OR 6.0 (95% CI 1.78 to 20.19)] P = 0.004. Patients, who did not fulfil all criteria, showed significantly higher rates of early mortality after eCPR initiation [OR 4.57 (95% CI 1.69 to 12.37)] P = 0.003. CONCLUSION: Patients fulfilling all inclusion criteria showed higher rates of survival after eCPR. Our results affirm that there is a possibility and even an obvious necessity for early patient selection based on standardised criteria before eCPR treatment. Large randomised trials are urgently needed to answer this question accurately.